Optimization of Islamic Institute Role in Promoting Sharia Banking in Indonesia - Awaluddin, Murtiadi; Suyuti, Muhammad Gazali; Awaluddin, Sri prilmayanti (Jurnal Minds: Manajemen Ide dan Inspirasi, 2020)
This study aims to provide recommendations for the optimization model of Islamic tertiary institutions' role in promoting Islamic banking development in Indonesia. This study uses a qualitative method with a phenomenological study and uses primary data obtained directly from the field (field research) at PTKI in Makassar. For secondary data, researchers investigated PTKI profiles in Makassar and respondents' perceptions of Indonesia's banking conditions. The results of this study suggest that Islamic higher education to preparing a ready to use human resources for the Islamic financial industry; to become a channel of education and financial knowledge in the financial behavior of students; and to perform the function as the Islamic literacy centre.